2014
DOI: 10.1017/s1355617714000927
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussive Symptoms and Neuropsychological Performance in the Post-acute Period following Pediatric Mild Traumatic Brain Injury

Abstract: In accordance with earlier studies, parents of children after mTBI initially observed significantly more PCS compared to parents of children after OI. There were no neuropsychological or socio-behavioral group differences between children after mTBI and OI in the post-acute period. However, our exploratory findings concerning the influence of everyday attention problems on neuropsychological outcome indicate that current and pre-injury everyday attention problems were negatively associated with neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Conversely, these data can be taken to highlight that 70% of children have relatively good outcome after 1 month and are on their way to full recovery. Prolonged symptom duration is increasingly being attributed to pre-morbid factors (Barlow, 2016), and substantial evidence suggests that significant cognitive and motor impairments are relatively rare and do not carry over in the mid to long term (Anderson et al, 2005;Asarnow et al, 1995;Babikian et al, 2011;Bijur & Haslum, 1995;Brooks et al, 2013;Fay et al, 1993;Hung et al, 2014;Rieger et al, 2013;Studer et al, 2014;Yeates, 2010). Using a statistically derived definition, Beauchamp and colleagues (2018) found that only about 10% of children who sustain concussion exhibit neuropsychological impairment 1 month post-injury.…”
Section: Course Of Symptom Cognitive and Psychosocial Recoverymentioning
confidence: 99%
“…Conversely, these data can be taken to highlight that 70% of children have relatively good outcome after 1 month and are on their way to full recovery. Prolonged symptom duration is increasingly being attributed to pre-morbid factors (Barlow, 2016), and substantial evidence suggests that significant cognitive and motor impairments are relatively rare and do not carry over in the mid to long term (Anderson et al, 2005;Asarnow et al, 1995;Babikian et al, 2011;Bijur & Haslum, 1995;Brooks et al, 2013;Fay et al, 1993;Hung et al, 2014;Rieger et al, 2013;Studer et al, 2014;Yeates, 2010). Using a statistically derived definition, Beauchamp and colleagues (2018) found that only about 10% of children who sustain concussion exhibit neuropsychological impairment 1 month post-injury.…”
Section: Course Of Symptom Cognitive and Psychosocial Recoverymentioning
confidence: 99%
“…There is controversy concerning the presence and evolution of concussion-related difficulties beyond the acute phase of recovery. A bulk of evidence suggests that children who sustain concussion do not show cognitive or motor deficits in the mid-to long-term on objective testing (Anderson, Catroppa, Morse, Haritou, & Rosenfeld, 2005;Asarnow et al, 1995;Babikian et al, 2011;Bijur & Haslum, 1995;Brooks et al, 2013;Fay et al, 1993;Hung et al, 2014;Rieger et al, 2013;Studer et al, 2014;; All manuscript authors contributed on behalf of the 5P Pediatric Emergency Research Canada Concussion (PERC) Team, which additionally includes the following members, all of whom were either involved in the study design, obtaining funding, and/or data collection analysis and interpretation for the main study: Jialing Xie, Jennifer Chatfield, Angelo Mikrogianakis, Stephen Freedman, Willem Meeuwisse (Alberta Children's Hospital/University of Calgary, Calgary, Canada); William Craig, Lawrence Richer, Nadia Dow (Stollery Children's Hospital, Edmonton, Alberta, Canada); Darcy Beer, Rena Papadimitropoulos, Terry Klassen, Tracey Levesque (Winnipeg Children's Hospital, Winnipeg, Manitoba, Canada); Gurinder Sangha, Cindy Langford (Children's Hospital of Western Ontario, London, Canada); Tinh Trung Tran (Hospital for Sick Children, Toronto, Ontario, Canada); Kenneth Tang, Ken Farion, Yael Kamil, Martin H Osmond, Michael Vassilyadi, Candice McGahern (Children's Hospital of Eastern Ontario, Ottawa, Canada); Vanessa DiGirolamo, and however, other reports reveal deficits not only acutely and in the short-term, but, in more limited cases, in the mid-to long-term (Babikian & Asarnow, 2009;Babikian et al, 2011;Gagnon, Swaine, Friedman, & Forget, 2004;Iverson, Brooks, Collins, & Lovell, 2006;McCauley et al, 2014;Nance, Polk-Williams, Collins, & Wiebe, 2009;Satz et al, 1997;Scherwath et al, 2011;Thomas et al, 2011). Discrepancies in results across studies may in part be related to differences in study participant characteristics, with some studies constrained to concussion (e.g., Babikian, McArthur, & Asarnow, 2013), and others including children with positive radiological findings (i.e., complicated mTBI; e.g., …”
mentioning
confidence: 99%
“…Though children with TBI were found to have deficits in inhibitory control processing in the stop-task similar to children with primary ADHD ( 53 ), there is mixed evidence as to if children with SADHD are especially impaired ( 37 , 38 , 40 , 41 , 53 ). New post-injury attention problems in children were associated with poorer verbal learning ( 35 ), short term memory ( 36 ), and working memory as well as planning ability ( 40 ). These neuropsychological impairments are summarized in Table 5 .…”
Section: Resultsmentioning
confidence: 99%